Detection of Babesia ovis by PCR in Rhipicephalus bursa collected from naturally infested sheep and goats - Altay, K.; Aktas, M.; Dumanli, N. (Elsevier Sci Ltd, 2008)
Polymerase chain reaction (PCR) was used to assess the presence and the frequency of Babesia ovis infection in the adult Rhipicephalus bursa and their hosts in Elazig province located in eastern Turkey. Tick and blood samples were collected from 32 sheep and 28 goats of four selected herds. A total of 226 R. bursa were randomly selected from the collected ticks and their salivary glands were dissected out in 0.85% saline under stereo microscope. DNA amplification method revealed that the frequency of B. ovis infections in the ticks and the small ruminants were 16.37% (37/226) and 6.66% (4/60), respectively. Three positive products, two of which were from the salivary glands of R. bursa and the other from sheep blood were purified from agarose gel and sequenced. The results showed that nucleotide sequences were identical to the previously reported nucleotide sequences of B. ovis. It is concluded that R. bursa might play an important role in the field as a natural vector of the parasite. (C) 2007 Published by Elsevier Ltd.
Keywords: Rhipicephalus bursa; sheep and goat; Babesia ovis; PCR